Optimalisasi Secondary Reserve terhadap Dana Simpanan Wadiah di PT Bank Syariah Indonesia - Faridatun Najiyah; Noor Iffatin Nadhifah (Dharma Ekonomi, 2024)
This study aims to analyze the influence of secondary reserves, which consist of placements in other banks, securities owned, and acceptance bills, on wadiah deposits at PT Bank Syariah Indonesia Tbk. using a quantitative approach with secondary data from the bank's monthly financial statements for the period 2022-2024. Researchers select relevant research subjects to obtain significant findings. The data were processed using descriptive statistical analysis and multiple linear regression with the help of the SPSS program to test the hypothesis. The results show that there is a significant influence of independent variables on dependent variables, which illustrates the importance of asset quality and fund management in increasing customer trust and, ultimately, the growth of deposits.